Significance of the dissection of common hepatic arterial lymph nodes in patients with oesophageal carcinoma: a multicentre retrospective study. Issue 1 (4th January 2022) - He, Huang-He; Hao, Zhexue; Li, Zhuoyi; Cheng, Fei; Fu, Junhui; Wang, Wei; He, Jiaxi; Luo, Jinhua; He, Jianxing
Abstract : Objectives: To explore the significance of intraoperative common hepatic arterial lymph node dissection in patients with ooesophageal squamous carcinoma (ESCC) without coeliac trunk lymph node metastasis indicated by abdominal enhanced CT. Methods: Patients aged 18–75 years who underwent oesophagectomy in three medical centres from June 2012 to June 2015, for whom R0 resection was completed and lymph node metastasis in the abdominal trunk was not identified before the operation were retrospectively analysed. The effects of the application value of common hepatic arterial lymph node dissection on survival were evaluated in patients with ESCC without coeliac trunk lymph node metastasis indicated by preoperative CT. According to the eighth version ofAmerican Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) staging, we selected patients with a Pathological Tumor Node Metastasis (pTNM) stage ranging from IA to IVA for analysis. Results: Among the 816 qualified patients, 577 did not have coeliac trunk lymph node metastasis based on preoperative abdominal enhanced CT, and common hepatic arterial lymph node dissection was performed during the operation (observation group). Two hundred and thirty-nine preoperative CT examinations indicated no coeliac trunk lymph node metastasis, and common hepatic arterial lymph node dissection was not performed during the operation (control group). A multifactor Cox proportional hazards model showed no risk factors for overall survival (OS) (adjusted HR (HRadj)=0.91; p=0.404) or disease-free survival (DFS) (HRadj=0.86; p=0.179), regardless of whether common hepatic arterial lymph node dissection was performed. For patients with positive left gastric arterial lymph node metastasis, a multifactor Cox proportional hazards model indicated that common hepatic arterial lymph node dissection was a risk factor for OS (HRadj=0.63; p=0.035) and DFS (HRadj=0.58; p=0.026). Conclusions: For patients with ESCC without celiac trunk metastasis indicated by abdominal enhanced CT, common hepatic arterial lymph node dissection conferred no survival benefits. However, for patients with left gastric arterial lymph node metastasis, common hepatic arterial lymph node dissection was beneficial.